Advances in Speech and Language Technologies for Iberian Languages IberSPEECH 2014 Conference, Las Palmas de Gran Canaria, Spain, November 19-21, 2014, Proceedings - Navarro Mesa, Juan Luis; Ortega, Alfonso; Teixeira, António; Hernández Pérez, Eduardo; Quintana Morales, Pedro; Ravelo Garcia, Antonio; Guerra Moreno, Iván; Toledano, Doroteo T. (Lecture Notes in Artificial Intelligence, 2014)
This book constitutes the refereed proceedings of the IberSPEECH 2014 Conference, held in Las Palmas de Gran Canaria, Spain, in November 19-21, 2014. The 29 papers presented were carefully reviewed and selected from 60 submissions. The papers are organized in topical sections on speech production, analysis, coding and synthesis; speaker and language characterization; automatic speech recognition; speech of language technologies in different application fields.